2013
DOI: 10.5539/gjhs.v5n3p1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Contraceptives Use amongst Youth: An Exploratory Study with Family Planning Service Providers in Karachi Pakistan

Abstract: Introduction:In Pakistan, Contraceptive Prevalence Rate (CPR) among married female youth is 17.4% and even lower in rural and slum areas leading to rapid population growth on one hand and poor health consequences on the other. The study was conducted to explore family planning service providers’ perceptions regarding use of different contraceptive methods and to identify factors that are influencing their use amongst currently married youth aged 18-24 years in slum areas of Karachi.Method:Qualitative explorato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…Nishtar et al, 17 found that with a good education, knowledge of contraception would also be good, so that 20 in Bangladesh which found that education is a significant factor to the contraseptives use, but all of these results were not in line with Walvekar, 21 study result which found no association between education of spouses with contraceptive use. Motivation is also one important factor in determining a choice in the use of contraceptives.…”
Section: Discussioncontrasting
confidence: 53%
“…Nishtar et al, 17 found that with a good education, knowledge of contraception would also be good, so that 20 in Bangladesh which found that education is a significant factor to the contraseptives use, but all of these results were not in line with Walvekar, 21 study result which found no association between education of spouses with contraceptive use. Motivation is also one important factor in determining a choice in the use of contraceptives.…”
Section: Discussioncontrasting
confidence: 53%
“…From programmatic view point, an encouraging aspect of increased knowledge and awareness of MWRA about contraceptive methods is the successful awareness raising efforts by MSS Field Health Educators who were the agents of information in this regard. This is encouraging programmatically since it shows that enhancing the capacity and efficacy of frontline workers can greatly impact perceptions about contraception that ultimately translate into increased and consistent usage of these methods [ 21 , 22 ]. Increased Awareness levels have also translated into the understanding and demand creation for contraception that is long term rather than shorter term methods indicated by enhanced IUD related Awareness and usage.…”
Section: Discussionmentioning
confidence: 99%
“…2 Being one of the poorest and sixth populous country in the world, Pakistan with other developing countries contributes 50% of the maternal deaths across the world. 3 It is expected that Pakistan's population will double by 2050. In spite of a long history of FP programs, the growth rate of population is high at 2.1%, with a contraceptive prevalence rate of 35%, unmet need at 20% and the total fertility rate at 3.8 4 With 35% CPR (according to Pakistan demographic health survey (PDHS) 2013), modern methods contributes only 26% and 20% of patients with an unmet need for family planning.…”
Section: Introductionmentioning
confidence: 99%